Iudicia bonae fidei - Sič, Magdolna (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
Iudicia bonae fidei is a civil procedure in which the judge has an ex officio obligation to safeguard bona fides, that is, to take into account the parties’ conduct demonstrated in their underlying relationship that lead to a dispute that was contrary to the principle of good faith. This duty of the judge is based on the praeteros’ formula: judge oblige the defendant to give or do whatever good faith requires (‘quidquid dare facere oportet ex fide bona’). The paper analyzes the much disputed issues of the emergence, legal basis as well as the function of this kind of procedure in Roman law.